Risk Factors for Low Birth Weight (LBW) Infants in East Nusa Tenggara (NTT) Province - Handayani, Sarah; Tsania, Febriani; Agus, Handito (Disease Prevention and Public Health Journal, 2024)
Background: The cause of infant mortality in East Nusa Tenggara (NTT) is 33% due to Low Birth Weight (LBW) infants, which is closely related to maternal nutrition and monitoring of pregnant women during pregnancy. This study aims to analyze the risk factors for LBW in East Nusa Tenggara Province in 2018 based on the 2018 Basic Health Research data results. Method: The research method used was quantitative with a Cross-sectional design. The population in the study totaled 1544 respondents. The sample in this study totaled 472 respondents. Univariate analysis aims to describe the data characteristics of each variable studied. Using the Chi-Square test, bivariate analysis was conducted to see the relationship between the independent and dependent variables.; Results: Variables associated significantly associated with the LBW infants in NTT Province in 2018 were the variables of education (ρ=0.034), parity (ρ=0.034), and gestational age (ρ=0.000). The dominant variable was Pregnancy Age (PR=2.613). The variable of gestational age was the most dominant risk factor associated with LBW infants with PR = 2.613 (95% CI = 1.525-4.478). The variable of gestational age has a three times greater risk of experiencing LBW infants in NTT Province in 2018. Conclusion: It is expected that health services and educational equality in rural areas in NTT Province should be further improved, especially maternal and child health. Maternal and child health, to improve the community's health status and reduce the morbidity and mortality rates of LBW infants